Idosos quilombolas: condições sociais e práticas de cuidados na atenção primária em município da baixada maranhense - COSTA, Andréa Suzana Vieira (2021)
Introduction: Brazil has a rapid aging process of its population. However, this occurs in conditions of socioeconomic and regional inequalities and with high health needs. One of the great challenges of this scenario is to ensure health care for elderly people living in remote areas, such as quilombola communities. These communities are in almost every state in Brazil, with Maranhão being the second with the largest number of them. Objectives: To analyze the social conditions and care practices of Primary Care, focused on the health of the elderly. The focus of the study was the quilombola communities of a municipality in Baixada Maranhense. Methods: The survey began at the end of the first half of 2018, with meetings with municipal managers, professionals from the Family Health teams and leaders of quilombola communities. Our objective is to present the project and align the research dynamics, collection schedule and feedback to the elderly and communities. The study was carried out in 11 remaining quilombola communities in the municipality of Bequimão - MA. These communities are officially recognized by the Palmares Cultural Foundation and by the Ministry of Culture in § 4 of art. 3 of Decree No. 4.887, of November 20, 2003. Thus, the communities of Ariquipá, Suassuí, Siberia, Pericumã, Juraraitá, Mafra, Santa Rita, Conceição, Ramal do Quidiua, Rio Grande and Marajá were included in the research. 212 elderly people were counted in this research. The communities with the highest number of elderly people were: Ariquipá (43), Ramal do Quindiua (34), Rio Grande (29), Pericumã (21), Santa Rita (21), Juraraitá (20) and Maraja (20). And those with the smallest number of elderly people are the quilombola communities of Conceição (8), Mafra (8), Siberia (4) and Sassui (4). In this study, a quantitative and qualitative approach was carried out in certified quilombola communities in the municipality of Bequimão, MA. In the quantitative approach, the number of elderly people aged 60 years or more, according to the list provided by the Community Health Agents (CHA) of each quilombola community, totaled 212 individuals. This study evaluated only 208 elderly people, due to refusals and difficulties in meeting such subjects in two attempts carried out on different dates. For data collection, the project's general questionnaire was used, which was based on the 2013 National Health Survey (PNS) questionnaire. After collecting the information, they were plotted and the data was analyzed using the Stata® version 14 program (StataCorp LP, College Station Texas, United States). The absolute and relative frequencies of the study variables were estimated. The prevalence of reported morbidities and multimorbidities (≥ 2 and ≥ 3 chronic diseases), controlled by sex and age, were presented. Fisher's Exact Test or Chi-square test was performed, and the differences considered statistically significant when p ≤ 0.05. The guiding problem of the qualitative research involved the following questions: How have care practices in Primary Care acted with users, specifically in the health of the elderly? What kind of traditional health practices exist in quilombola communities? Do Family Health Strategy professionals establish any dialogue with traditional health practices? Therefore, to understand these issues we use the ethnographic method. In addition to the bibliographic survey, the field work was carried out using the technique of participant observation, which was recorded in a field diary. We started by mapping the communities covered by these teams and the BHU of reference for serving the general population and the elderly. Each community studied, as well as other popular health practices existing in the localities, were evaluated. Soon after, visits to monitor the Family Health teams were scheduled within a monthly schedule prepared by the team. The visits to BHU in Areal, Quindiua and Santana were made in July 2019. We went to BHU de Conceição at the end of August. The field work included visits to the communities to monitor the SF teams, aiming to experience the daily life of the community. This allowed us not only to observe, but mainly to socialize, talk and, above all, listen to health professionals and community members about their memories, perspectives, and points of view. Results: In the first article, the results showed that most of the elderly quilombolas live in a precarious socioeconomic, sanitary and health situation, among them the prevalence of multimorbidities was high. In the second article, it is observed that the conditions and the work process to which the workers of the Family Health Strategies (FHS) are submitted revealed the difficulties in the production and continuity of the health service offer. We realized that care for the elderly was centered on nosological issues. Actions to establish dialogue between health professionals and elderly practitioners of popular knowledge were almost non-existent. Conclusion: The results indicate the need for effective actions that manage to reduce these inequalities and weaknesses that compromise the well-being and quality of life of the elderly. The lack of health care for the elderly quilombolas, the conditions and the work process to which the workers of the Family Health Strategy (FHE) are subjected have hindered the production and continuity of the health service offer. In addition, there are timid actions to establish a dialogue between practices and health professionals with care specialists based on popular knowledge.